Anthricin-induced hyperactive proteasome and its molecular mechanism - Kotaro Sakamoto; Runa Fujimoto; Erina Kamiyama-Ando; Takatsugu Hirokawa (Biochemistry and Biophysics Reports)
Recently, targeted protein degradation has attracted increasing interest as a new drug discovery approach. This method aims to control the function of drug targets by inducing their degradation through protein degradation systems such as the proteasome. Concurrently, compounds that enhance proteasome activity have also garnered attention. In 2023, we reported that anthricin (also known as 4-deoxypodophyllotoxin), a natural product that belongs to the lignan family, enhances proteasome activity. However, whether this enhancement was because of increased proteasome expression or improved proteasome function remains unclear. In this study, we investigated the structure–activity relationship of anthricin and its analogs in enhancing proteasome activity, the effects of anthricin on proteasome-related gene expression, and the direct binding between anthricin and the proteasome using pull-down assay. Moreover, we assessed the interaction between anthricin and the proteasome using molecular dynamics (MD) simulations. The results showed that anthricin does not induce proteasome-related gene expression, but instead binds to the β-subunit of the proteasome, bringing the side chains of three amino acid residues (Thr1, Asp17, and Lys33) at the catalytic site closer together, thereby inducing a hyperactive state. To the best of our knowledge, this study is the first to suggest the mechanism of proteasome activity enhancement by anthricin at the molecular level. The findings could contribute to the development of new chemotypes to enhance the effects of targeted protein degraders by regulating proteasome activity.